The “structurally minimal” isoform KChIP2d modulates recovery of K(v)4.3 N-terminal deletion mutant Δ2-39 - Hovind, Laura J (Landes Bioscience, 2011)
Mechanisms underlying K(v)4 (Shal type) potassium channel macroscopic (open state) inactivation and recovery are unknown, as are mechanisms by which KChIP2 isoforms modulate these two processes. In a recent study (Xenopus oocytes, 2 microelectrode voltage clamp) we demonstrated that: i) Partial deletion of the K(v)4.3 proximal N-terminal domain (Δ2-39; deletes N-terminal amino acids 2–39) not only slowed macroscopic inactivation, but also slowed the net rate of recovery; and ii) Co-expression of KChIP2b significantly accelerated the rate Δ2-39 recovery from inactivation. The latter effect demonstrated that an intact N-terminal domain was not obligatorily required for KChiP2b-mediated modulation of K(v)4.3 recovery. To extend these prior observations, we have employed identical protocols to determine effects of KChiP2d on Δ2-39 macroscopic recovery. KChiP2d is a “structurally minimal” isoform (consisting of only the last 70 amino acids of the common C-terminal domain of larger KChIP2 isoforms) that exerts functional modulatory effects on native K(v)4.3 channels. We demonstrate that KChiP2d also accelerates Δ2-39 recovery from macroscopic inactivation. Consistent with our prior Δ2-39 + KChIP2b study, these Δ2-39 + KChIP2d results: i) Further indicate that KChIP2 isoform-mediated acceleration of K(v)4.3 macroscopic recovery is not obligatorily dependent upon an intact proximal N-terminal; and ii) Suggest that the last 70 amino acids of the common C-terminal of KChiP2 isoforms may contain the domain(s) responsible for modulation of recovery.